Challenges in the achievement of a Net Zero Carbon Built Environment – A systemic approach to support the decision-aiding process in the design stage of buildings. Issue 3 (November 2020) - Scherz, Marco; Passer, Alexander; Kreiner, Helmuth
Abstract: By limiting global warming to 2°C, the climate goals set by the United Nations in 2015 (Agenda 2030) will clearly be missed. The shrinking of our GHG budget has shown that the implementation of a weak sustainability concept - i.e. equal consideration of all sustainability dimensions (environmental, economic and social) - is not sufficient to meet the requirements of the Sustainable Development Goals (SDGs). Based on the strong sustainability concept - i.e. focusing on the environmental dimension of sustainability - this article highlights the challenges in the achievement of a Net Zero Carbon Built Environment by the implementation of a systemic design model in the early design stage of buildings. The visualisation of individual planning practices and their systemic behaviour in relation to other planning practices respectively to the SDGs support planners to manage the complexity and to reduce the additional effort within the implementation of sustainability aspects in the early design stage of buildings. Next to the visualisation of the environmental impacts of planning practices, the effects on other SDGs can be highlighted. Furthermore, the planner is supported in the decision-aiding processes in the early design stage. With the application of the systemic design model and the implementation of identified planning practices the contribution to the fulfilment of Agenda 2030 increases.